A Model of Economic Evaluation for the Acquisition of Flexible Manufacturing Technologies - Palominos-Belmar, P; Quezada-Llanca, L; Donoso-Oyarzun, J (Elsevier B.V., 2019)
Manufacturing companies have to withstand a growing global competition on different strategic dimensions like production costs, product quality, flexible manufacturing and product innovation. To cope with this increased competition, companies invest in solutions based on flexible idea, as flexible assembly systems, flexible selection and picking systems, automated warehouses, etc. However, the high level of technical sophistication and the high investment of this type of technology make the selection of flexible technologies difficult. A linear programming model is proposed, based on the concepts of manufacturing flexibility to make investment decisions when manufacturing multiple products. Finally, we present a numerical example in which optimal acquisition decisions and the value of flexibility are calculated in the context of the decision to invest in the manufacturing plant. © 2019 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0/)